Fly Guy presents : dogs - Arnold, Tedd (New York, NY : Scholastic Inc., 2022)
While visiting a dog show, Buzz and Fly Guy learn all about man's best friend! From exploring different breeds, to famous dogs throughout history, to learning all about working dogs and more, there's plenty for the best friends to explore.
School Library Journal, September 2022
4.4
K-3
Keywords: Dogs -- Juvenile literature; Dog breeds -- Juvenile literature; Dogs; Dog breeds